2020
DOI: 10.1103/physrevx.10.011015
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics of Human Aortas for Material Characterization

Abstract: Evaluating the nonlinear dynamics of human descending thoracic aortas is essential for building the next generation of vascular prostheses. This study characterizes the nonlinear dynamics, viscoelastic material properties, and fluid-structure interaction of 11 ex-vivo human descending thoracic aortas the full range of physiological heart rates. The aortic segments are harvested from heart-beating donors screened for transplants. A mock circulatory loop is developed to reproduce physiological pulsatile pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
1
22
1
Order By: Relevance
“…The aorta is subjected to cyclic pulsatile pressure at a frequency in the range of 1 to about 3 Hz (i.e., 60 to 180 beats per minute). The pulsatile pressure is not harmonic ( 3 ), but it can be expanded in a Fourier series with harmonic components. In this study, the strips were loaded by a harmonic cyclic strain with an amplitude of 7% of their length.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aorta is subjected to cyclic pulsatile pressure at a frequency in the range of 1 to about 3 Hz (i.e., 60 to 180 beats per minute). The pulsatile pressure is not harmonic ( 3 ), but it can be expanded in a Fourier series with harmonic components. In this study, the strips were loaded by a harmonic cyclic strain with an amplitude of 7% of their length.…”
Section: Resultsmentioning
confidence: 99%
“…Prosthetic tubes made of polyester (Dacron) or polytetrafluoroethylene are often used for the surgical repair of large arteries in aneurysms or acute dissection. Unfortunately, these grafts are so stiff to diameter expansion ( 3 ) that they can cause cardiovascular and perfusion problems because they fail to reduce the highly pulsatile nature of the blood flow exiting the heart. This is the reason for an increasing interest in the development of a new generation of grafts ( 4 ) in innovative biomaterials or in tissue engineering that mimic the dynamic behavior of the aorta, which is achieved through the correct adjustment of mechanical properties and the introduction of a layered design.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, nonlinear dissipation has attracted much attention with applications that span nanomechanics 1 , materials science 2 , biomechanics 3 , thermodynamics 4 , spintronics, 5 and quantum information 6 . It has been shown that the nonlinear dissipation process follows the empirical force model where τ nl1 is the nonlinear damping coefficient, x is the displacement, and velocity.…”
Section: Introductionmentioning
confidence: 99%
“…[9,[14][15][16][17]) are comparatively scarce despite the pulsatile nature of blood flows. A notable exception is Amabili et al's recent study [18] in which part of an excised human aorta was mounted between two rigid pipes and subjected to physiological pulsatile pressure and flow rates.…”
mentioning
confidence: 99%